2014
DOI: 10.1002/jsfa.6700
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Geobacillus stearothermophilus spores in low-acid foods by pressure-assisted thermal processing

Abstract: The complex food matrices caused a protective effect on the inactivation of G. stearothermophilus spores during PATP. The results provide useful information in inactivation kinetics of bacterial spores for validating PATP-processed low-acid foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…No clear trend was observed for the used medium, but this factor had a significant impact on the reduction of the spore‐forming bacterium. The removal properties of supports were expected to be higher in a simple medium, like water, than in broth due to the presence of peptides or sugars that can provide a protective effect for the microorganism (Ahn et al., 2015). However, this effect may be very slight as cells were not incubated in the media for a long time, but only for the time required to filter the sample.…”
Section: Resultsmentioning
confidence: 99%
“…No clear trend was observed for the used medium, but this factor had a significant impact on the reduction of the spore‐forming bacterium. The removal properties of supports were expected to be higher in a simple medium, like water, than in broth due to the presence of peptides or sugars that can provide a protective effect for the microorganism (Ahn et al., 2015). However, this effect may be very slight as cells were not incubated in the media for a long time, but only for the time required to filter the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have acknowledged the good fit and flexibility of WBLL, which is reflected in its recent application to predict high pressure kinetics of microbial spore inactivation (Ahn et al . ) and chemical compound degradation (Martínez‐Monteagudo and Saldaña , ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies in which R 2 , MSE and the accuracy factor remained as the preferred statistics for model selection also selected WBLL as the best alternative to model HPP microbial inactivation kinetics (Chen and Hoover 2003;Buzrul et al 2005;Chen 2007). Researchers have acknowledged the good fit and flexibility of WBLL, which is reflected in its recent application to predict high pressure kinetics of microbial spore inactivation (Ahn et al 2015) and chemical compound degradation (Mart ınez-Monteagudo and Saldaña 2014b, 2015).…”
Section: Statistical Analysis Of Hpp Microbial Inactivation Kinetic Mmentioning
confidence: 99%
“…For example, Patazca and others () and Wang and others () verified that a log‐linear regression model described well the inactivation kinetics of both G. stearothermophilus and B. coagulans spores, respectively. Rajan and others (), Tola and Ramaswamy (), and Ahn and others () observed that PATS inactivation of B. stearothermophilus , B. licheniformis , and G. stearothermophilus spores, respectively, did not exhibit a linear inactivation kinetics, with the Weibull model being the best model to describe PATS inactivation in these 3 cases. In contrast, Shao and Ramaswamy () observed 1st‐order kinetics during holding time for the destruction of C. sporogenes spores.…”
Section: Novel Sterilization Technologiesmentioning
confidence: 96%
“…In another study, spores of G. stearothermophilus were suspended in deionized water and in several food products, such as cooked ground beef, egg patty mince, whole milk, and mashed potatoes. These samples were treated by PATS (500 to 700 MPa and 105 °C during 0 to 5 min) and different spore resistances were observed in the different food matrices during the come‐up time (Ahn and others ). Similarly, spore destruction during holding time varied according to the food matrix and was affected by different pressure levels.…”
Section: Novel Sterilization Technologiesmentioning
confidence: 99%